Improving exposition writing proficiency through the application of problem based learning method for senior high school students - Rasyimah, Rasyimah; Ayadi, Ayadi; Sari, Dewi Kumala (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
The low level of proficiency among students, coupled with the fact that teaching writing in schools in particular receives little attention, is the driving reason behind the research. The majority of students psychologically perceive writing assignments as a hardship since they feel less capable of using the Indonesian language accurately and effectively. Teachers typically lack variety in the methods they use from a methodological standpoint. These factors led to the use and testing of a problem-based learning approach at SMA Negeri No 2 Dewantara, North Aceh. This study sought to ascertain whether problem-based learning techniques could enhance students' expository writing skill. From the result, it can be inferred that there are differences between how well students who learn using the PBL model and those who learn using a traditional approach write exposition texts. The pupils in the experimental class's mean post-test score of 91.3 serves as evidence for this. This is greater than the control class students' post-test mean score of 62.0. It is concluded that using a problem-based approach enhances students' ability to produce expositions that adhere to the exposition's criteria.